2021
DOI: 10.1103/physrevd.103.063513
|View full text |Cite
|
Sign up to set email alerts
|

Atacama Cosmology Telescope: Combined kinematic and thermal Sunyaev-Zel’dovich measurements from BOSS CMASS and LOWZ halos

Abstract: The scattering of cosmic microwave background (CMB) photons off the free-electron gas in galaxies and clusters leaves detectable imprints on high resolution CMB maps: the thermal and kinematic Sunyaev-Zel'dovich effects (tSZ and kSZ respectively). We use combined microwave maps from the Atacama Cosmology Telescope DR5 and Planck in combination with the CMASS (mean redshift hzi ¼ 0.55 and host halo mass hM vir i ¼ 3 × 10 13 M ⊙ ) and LOWZ (hzi ¼ 0.31, hM vir i ¼ 5 × 10 13 M ⊙ ) galaxy catalogs from the Baryon O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
131
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 79 publications
(175 reference statements)
3
131
0
Order By: Relevance
“…The kSZ measurements [8,18] have traced the distribution of free electrons around galaxies using independent measurements of the peculiar velocity from the galaxy overdensity field. Combining CMB data from the Atacama Cosmology Telescope (ACT) with individual velocity estimates from the "constant stellar mass" (CMASS) catalog of the Baryon Oscillation Spectroscopic Survey (BOSS DR10) [19], they showed that the gas density profiles in groups deviate significantly from a "dark matter only" Navarro-Frenk-White profile (NFW) [20] expected in the absence of feedback.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The kSZ measurements [8,18] have traced the distribution of free electrons around galaxies using independent measurements of the peculiar velocity from the galaxy overdensity field. Combining CMB data from the Atacama Cosmology Telescope (ACT) with individual velocity estimates from the "constant stellar mass" (CMASS) catalog of the Baryon Oscillation Spectroscopic Survey (BOSS DR10) [19], they showed that the gas density profiles in groups deviate significantly from a "dark matter only" Navarro-Frenk-White profile (NFW) [20] expected in the absence of feedback.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use the new stacked tSZ and kSZ measurements obtained in a companion paper [18] by cross-correlating the CMASS galaxy catalogs of BOSS DR10 [19] and temperature maps from combined ACT DR5 and Planck data from [44] in the f150 and f090 bands (centered at roughly 150 GHz and 98 GHz, respectively) to constrain the baryonic processes, such as feedback and nonthermal pressure support, and the thermodynamic profiles of the CGM/ICM. Our models include a correction for the contamination of the tSZ signal by the thermal emission of dust from galaxies in our sample, which we estimate from ACT DR5 (f090, f150) and Herschel/H-ATLAS data [45] in the three bands centered at 500 μm (600 GHz), 350 μm (857 GHz), and 250 μm (1200 GHz).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimally combining data from the ACT-MBAC, ACTPol, and AdvACT surveys as well as Planck, the DR5 co-added maps cover the same total ∼18,000 deg 2 sky footprint as DR4 but with a full co-added depth of 10 mK CMB ′ over ∼2500 deg 2 . These maps are ideal for producing cluster catalogs, such as in Section 3.9, and are well suited for stacking analyses such as measurements of the tSZ and kinematic Sunyaev-Zel'dovich (kSZ) effects (Amodeo et al 2021;Schaan et al 2021;Calafut et al 2021;Vavagiakis et al 2021), cluster lensing (Madhavacheril et al 2020b), point-source and cluster studies, and Galactic science. Due to the preliminary nature of the s17-s18 data, the DR5 co-added maps are not recommended for precision cosmology.…”
Section: Dr5 Co-added Maps 52mentioning
confidence: 99%